Jobless growth: empirical evidences from the Middle East and North Africa region - Mohamad A. Abou Hamia (Journal for Labour Market Research, 2016)
In this study, we use Okun's Law to examine whether growth has been jobless in seventeen MENA countries. The methods used are the ARDL approach for the individual country and the panel data analysis for the entire sample. The period considered in this study is from 1980 to 2013. To test for results robustness, we estimate the dynamic difference and three gap models based on three de-trending techniques: the HP filter, the BK filter, and the quadratic trend. Our findings can be summarized as follows: First, the estimation results suggest that Okun's Law is valid, and hence job creation is associated with growth in only six of the seventeen countries, namely Algeria, Egypt, Iran, Jordan, Lebanon, and Turkey. Second, our results reveal that the valid estimates are, in general, bigger in Arab than non-Arab countries in the sample. Third, the CUSUM of squares test confirms that Okun's Law is stable in Algeria, Egypt, and Iran, unstable in Jordan, and ambiguous in Lebanon and Turkey. Fourth, our panel data analyses suggest that Okun's Law is valid for the entire MENA sample; however, our estimations reveal that the impact of GDP growth is weak on job creation in the region. Finally, our individual and panel estimations are not robust as they are sensitive to the choice of the estimation model and to the de-trending method.
Keywords: E24; E32; J01; 330; Okun's Law; Wirtschaftswachstum; Beschäftigungsentwicklung; Beschäftigungseffekte - internationaler Vergleich; Arbeitslosigkeitsentwicklung; Bruttoinlandsprodukt; Nahost; Nordafrika; Algerien; Bahrain; Ägypten; Iran; Jordanien; Kuwait; Libanon; Marokko; Oman; Katar; Saudi-Arabien; Sudan; Syrien; Tunesien; Türkei; Jemen; Vereinigte Arabische Emirate